2016
DOI: 10.1021/jacs.6b01805
|View full text |Cite
|
Sign up to set email alerts
|

A Light-Activated Reaction Manifold

Abstract: We introduce an efficient reaction manifold where the rate of a thermally induced ligation can be controlled by a photonic field via two competing reaction channels. The effectiveness of the reaction manifold is evidenced by following the transformations of macromolecular chain termini via high-resolution mass spectrometry and subsequently by selective block copolymer formation. The light-controlled reaction manifold consists of a so-called o-quinodimethane species, a photocaged diene, that reacts in the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Red light passed through skin and tissue and then induced the release of [Ru(CHLtpy)(biq)(H 2 O)] 2+ for PACT. Red‐light‐responsive PEG‐ b ‐P(CPH‐ co ‐RuCHL) is better suited than conventional UV or short‐wavelength visible light‐responsive polymers for biomedical applications because red light can penetrate deeper into tissue . We have demonstrated that red light activated Ru complexes with similar responsive wavelengths to PEG‐ b ‐P(CPH‐ co ‐RuCHL) after red light passed through tissue with a thickness up to 16 mm .…”
Section: Introductionmentioning
confidence: 97%
“…Red light passed through skin and tissue and then induced the release of [Ru(CHLtpy)(biq)(H 2 O)] 2+ for PACT. Red‐light‐responsive PEG‐ b ‐P(CPH‐ co ‐RuCHL) is better suited than conventional UV or short‐wavelength visible light‐responsive polymers for biomedical applications because red light can penetrate deeper into tissue . We have demonstrated that red light activated Ru complexes with similar responsive wavelengths to PEG‐ b ‐P(CPH‐ co ‐RuCHL) after red light passed through tissue with a thickness up to 16 mm .…”
Section: Introductionmentioning
confidence: 97%
“…Phototherapy causes minimal side effects for normal tissues because light provides high spatial resolution and allows activation of the phototherapeutic agents at target sites only . Most photoresponsive materials, such as photoactivated platinum, coumarin‐caged and pyrene‐caged prodrugs are sensitive to UV or short‐wavelength visible light. However, UV or short‐wavelength visible light is problematic for biomedical applications, because these wavelengths cannot penetrate deeply into tissue .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the exploitation of different colors of light as a gate to switch between thermally and photochemically activated reaction channels is almost non-explored and constitutes a key next frontier within the realm of reaction control 31 . Indeed, simply selecting the outcome of chemical one-pot processes by the absence or presence of a photonic field or by different wavelengths will allow for the development of, e.g., sub-diffraction photoresists 32 34 or multi-area-selective surface lithography.…”
Section: Introductionmentioning
confidence: 99%